Food security, nutrition and public distribution (social goals and flawed delivery systems) - Dhar, T.N. (2005)
The food security for the country has to counter several roadblocks like production, pricing, procurement, open market availability, distribution and nutritional balance. The food management, as an essential need, has so far been done through continued and rising government intervention in the foodgrain markets. This intervention has shown food results but many negatives have crept into the realm of this policy causing some adverse economic impacts, financial burden on central exchequer and price distortions. An indepth analysis here funds that we have at present an economically unfeasible and politically unsustainable food management policy that needs quick corrections. The article suggests that entire food security policy including foodgrain procurement and distribution system needs a fresh look and substantial policy change based on logical facts and political consensus. -Reproduced.
Keywords: Public distribution system; Nutrition; Food supply